2020
DOI: 10.11606/s1518-8787.2020054001693
|View full text |Cite
|
Sign up to set email alerts
|

The case of eculizumab: litigation and purchases by the Brazilian Ministry of Health

Abstract: OBJECTIVES: This study examined the purchases of eculizumab, a high-cost monoclonal antibody used in the treatment of rare diseases by Brazilian federal agencies, in terms of purchased quantities, expenditures, and prices. METHODS: Eculizumab purchases made between March 2007 and December 2018 were analyzed, using secondary data extracted from the Federal Government Purchasing System (SIASG in Portuguese). The following aspects were assessed: number of purchases, purchased quantities, number of daily doses def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 26 publications
0
13
0
3
Order By: Relevance
“…APURASUS, SIGAF and SIASG are used by different levels of government to control costs and transmit information from local systems to the national level to plan acquisition and distribution. For example, SIASG made it possible to explore expenditures, pricing and judicial demands for a variety of drugs and drug classes, and it has been important for decision-making about the incorporation of drugs in the national list and the sustainability of provision programs ( Luo et al, 2014 ; Chaves et al, 2017 ; Chama Borges Luz et al, 2017 ; Magarinos-Torres et al, 2017 ; dos Santos Teodoro et al, 2017 ; Alves et al, 2018 ; Caetano et al, 2020 ; dos Santos Dias et al, 2020 , 2009–2017; Matos et al, 2020 ). However, the safety profile of medicines and outcomes in the population cannot be examined with these data.…”
Section: Discussionmentioning
confidence: 99%
“…APURASUS, SIGAF and SIASG are used by different levels of government to control costs and transmit information from local systems to the national level to plan acquisition and distribution. For example, SIASG made it possible to explore expenditures, pricing and judicial demands for a variety of drugs and drug classes, and it has been important for decision-making about the incorporation of drugs in the national list and the sustainability of provision programs ( Luo et al, 2014 ; Chaves et al, 2017 ; Chama Borges Luz et al, 2017 ; Magarinos-Torres et al, 2017 ; dos Santos Teodoro et al, 2017 ; Alves et al, 2018 ; Caetano et al, 2020 ; dos Santos Dias et al, 2020 , 2009–2017; Matos et al, 2020 ). However, the safety profile of medicines and outcomes in the population cannot be examined with these data.…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, a specialized evaluation was requested from the Brazilian Institute of Health (CONITEC) to incorporate the medication into the public health system. However, in 2019 CONITEC concluded that eculizumab was not suitable to be incorporated into the public health system due to the high cost of this therapy [ 29 ]. For this reason, currently, in Brazil, the only way to access eculizumab is through judicialization, which in this country is a lengthy process and that delays the beginning of the treatment in months [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of this information is relevant to Brazil, which is ranked at the first position in the number of transplants performed by the Brazilian public health system (SUS) [ 31 ] and reserves for this purpose an annual budget around R$1 billion [ 31 ]. In this context, the use of a high-cost medication such as eculizumab, which acquisition expenditure by the Brazilian government in the year 2016 was R$624,621,376.84 (60% of the annual budget destined for transplantation) may jeopardize the sustainability of the health program [ 29 ]. Thus, an ethical dilemma is imposed on the use of a high-cost medication, but that shows great efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…In December 2018, the drug was included on public funding lists, exclusively for the treatment of PNH [ 92 ]. The clinical protocol that ensures patient access to the drug under the public health system and regular procurement was published only in November 2019 [ 93 ], effectively meaning that procurement up to December 2019 was subject to bidding waiver (152,209 vials purchased by the Ministry of Health for US$8,563,184,381.05) [ 94 ].…”
Section: Discussionmentioning
confidence: 99%